A escrita demiúrgica de Clarice Lispector - Linné, Vinícius (2013)
Writing has always been a reason for speculation for some writers, who are anxious to understand the motivations and the effects of their own work. Even among these curious authors, only a few of them have deepened in arcane literary creation as Clarice Lispector did. Although this subject is present in most of her novels, is only in her final book, Um sopro de vida (pulsações), published posthumously, where Lispector effectively addressed this point. In a book without a plot, or timeframe, which is close to what Rosenfeld (1968) called "Modern Romance", just the reflections about the creating act interest the author. The book was chosen to be the corpus of this dissertation to explore the hypothesis that Lispector puts herself in the position of a God to her characters. This is done by comparing the narrative and the story of creation contained in Genesis, first book of the Bible. It can be seen that within the fictional plane, Lispector could be both the creator and the creature, transmuting into an anonymous character, cited only as Author (a simulacrum of God) and fictionalizing herself as Ângela Pralini in the creation of this fictional author. For this analysis it s necessary to invoke, through Cassirer (1925), the historical relations between the mythology of the demiurgic creation and the word itself, which is always figuring as a tool for the creation of the universe and life. Just as God, it s possible to realize that the author, using his words, does not describe or say something that already exists, but he creates something totally new. This meaning also leads to the concepts of Austin (1962) about performing sentences, which do not amount to any findings, but rather a real action. The same concept designed for speech acts can also be applied to literary writing, as the author, when writing, promotes creation and modification within their fictional universe. At last, is the analysis of the writer s characteristics at the time of its work composition, with similar characteristics to those commonly ascribed to God: omniscience, omnipresence, omnipotence and immortality